Dissociating nouns and verbs in temporal and perisylvian networks: Evidence from neurodegenerative diseases. (September 2021) - Lukic, Sladjana; Borghesani, Valentina; Weis, Elizabeth; Welch, Ariane; Bogley, Rian; Neuhaus, John; Deleon, Jessica; Miller, Zachary A.; Kramer, Joel H.; Miller, Bruce L.; Dronkers, Nina F.; Gorno-Tempini, Maria L.
Abstract: Naming of nouns and verbs can be selectively impaired in neurological disorders, but the specificity of the neural and cognitive correlates of such dissociation remains unclear. Functional imaging and stroke research sought to identify cortical regions selectively recruited for nouns versus verbs, yet findings are inconsistent. The present study investigated this issue in neurodegenerative diseases known to selectively affect different brain networks, thus providing new critical evidence of network specificity. We examined naming performances on nouns and verbs in 146 patients with different neurodegenerative syndromes (Primary Progressive Aphasia – PPA, Alzheimer's disease – AD, and behavioral variant Frontotemporal Dementia – FTD) and 30 healthy adults. We then correlated naming scores with MRI-derived cortical thickness values as well as with performances in semantic and syntactic tasks, across all subjects. Results indicated that patients with the semantic variant PPA named significantly fewer nouns than verbs. Instead, nonfluent/agrammatic PPA patients named fewer verbs than nouns. Across all subjects, performance on nouns (adjusted for verbs) specifically correlated with cortical atrophy in left anterior temporal regions, and performance on verbs (adjusted for nouns) with atrophy in left inferior and middle frontal, inferior parietal and posterior temporal regions. Furthermore, lower lexical-semantic abilities correlated with deficits in naming both nouns and verbs, while lower syntactic abilities only correlated with naming verbs. Our results show that different neural and cognitive mechanisms underlie naming of specific grammatical categories in neurodegenerative diseases. Importantly, our findings showed that verb processing depends on a widespread perisylvian networks, suggesting that some regions might be involved in processing different types of action knowledge. These findings have important implications for early differential diagnosis of neurodegenerative disorders.